Study on gas flow network analysis at Shah Alam Industrial area by using Cox's method - Nik Fazdrul, Nik Hussin (2012)
Natural gas is a vital component of the world's supply of energy.It is one of the cleanest,safest,and most useful of all energy sources.In industry,natural gas is used as an input to manufacture pulp and paper, metals,chemicals, stone, clay,glass,and to process certain foods. Natural gas is also used to treat waste materials,for incineration, drying, dehumidification, heating and cooling,and cogeneration.The major transportation of natural gas is carried through pipelines.High demand for natural gas primarily to the customers who live in big cities around the world.This also happens in major cities in Malaysia.Gas transport networks around Shah Alam present a large set of highly integrated pipe networks operating over a wide range of pressures. Growing demand for gas makes it necessary to adapt and expand these systems while ensuring safe delivery and cost-effective engineering.To avoid from the natural gas was stop from supply the gas supply and to make sure the continuity and reliability to the consumers the pressure drop for each junction of the pipeline must be decrease.At one time the method of solving network flow problem was a manual trial-and-error procedure by doing Cox’s method.In this method, the pressure drop and pipe size of each pipeline can be determined for each junction of the pipe. The parameters needed to calculate the pressure drop are flow rate, distance,pipe size,specific gravity and pressure inlet.From this research, the pressure drop from Cox’s method calculation is less than pressure drop calculation from NFPA method by Gas Malaysia Berhad.